Longitudinal changes in body composition and resting metabolic rate in male professional flat jockeys: preliminary outcomes and implications for future research directions - Wilson, G.; Langan-Evans, C.; Martin, D.; Kasper, A. M.; Morton, J. P.; Close, G. L. (International Journal of Sport Nutrition and Exercise Metabolism, 2023)
Jockeys are unique given that they make weight daily and, therefore, often resort to fasting and dehydration. Through increasing daily food frequency (during energy deficit), we have reported short-term improvements in jockey`s body composition. While these changes were observed over 6-12 weeks with food provided, it is unclear whether such improvements can be maintained over an extended period during free-living conditions. We, therefore, assessed jockeys over 5 years using dual X-ray absorptiometry, resting metabolic rate, and hydration measurements. Following dietary and exercise advice, jockeys reduced fat mass from baseline of 7.1 ± 1.4 kg to 6.1 ± 0.7 kg and 6.1 ± 0.6 kg (p < .001) at Years 1 and 5, respectively. In addition, fat-free mass was maintained with resting metabolic rate increasing significantly from 1,500 ± 51 kcal/day at baseline to 1,612 ± 95 kcal/day and 1,620 ± 92 kcal/day (p < .001) at Years 1 and 5, respectively. Urine osmolality reduced from 816 ± 236 mOsmol/L at baseline to 564 ± 175 mOsmol/L and 524 ± 156 mOsmol/L (p < .001) at Years 1 and 5, respectively. The percent of jockeys consuming a regular breakfast significantly increased from 48% at baseline to 83% (p = .009) and 87% (p = .003) at Years 1 and 5, alongside regular lunch from 35% to 92% (p < .001) and 96% (p < .001) from baseline to Years 1 and 5, respectively. In conclusion, we report that improved body composition can be maintained in free-living jockeys over a 5-year period when appropriate guidance has been provided.